Employee Performance in Public Service: Effects of Leadership, Work Environment, and Motivation - Yuyun Sri Rahayu; Popy Novita Pasaribu; Azis Firdaus (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of leadership style, work environment, and work motivation on employee performance at the Department of Population and Civil Registration of Bogor Regency and to examine differences between civil servants (ASN) and non-civil servants (non-ASN). This research contributes to the understanding of factors affecting employee performance within public sector organizations. A quantitative approach with an associative-causal and cross-sectional design was employed. Data were collected from employees through questionnaires, supported by observation and interviews, and analyzed using descriptive and inferential statistical techniques. The findings indicate that leadership style, work environment, and work motivation positively influence employee performance, both individually and collectively. Among these factors, the work environment was identified as the most influential determinant of employee performance. The study also reveals variations in the influence of these factors between ASN and Non-ASN employees, reflecting differences in organizational and employment characteristics. These findings highlight the importance of creating a supportive work environment, implementing effective leadership practices, and fostering employee motivation to enhance organizational performance and public service quality. The study provides practical implications for public sector managers in designing strategies to improve employee performance and organizational effectiveness.